Modeling of Stacking Fault Energy in Hexagonal-Close-Packed Metals - Zhigang Ding; Shuang Li; Wei Liu; Yonghao Zhao (Advances in Materials Science and Engineering)
The deformation of metals is known to be largely affected by their stacking fault energies (SFEs). In the review, we examine the theoretical background of three normally used models, supercell model, Ising model, and bond orientation model, for the calculation of SFE of hexagonal-close-packed (hcp) metals and their alloys. To predict the nature of slip in nanocrystalline metals, we further review the generalized stacking fault (GSF) energy curves in hcp metals and alloys. We conclude by discussing the outstanding challenges in the modeling of SFE and GSF energy for studying the mechanical properties of metals.